Brown Carbon Fuel and Emission Source Attributions to Global Snow Darkening Effect. (18th April 2022) - Brown, Hunter; Wang, Hailong; Flanner, Mark; Liu, Xiaohong; Singh, Balwinder; Zhang, Rudong; Yang, Yang; Wu, Mingxuan
Abstract: Snow and ice albedo reduction due to deposition of absorbing particles (snow darkening effect [SDE]) warms the Earth system and is largely attributed to black carbon (BC) and dust. Absorbing organic aerosol (BrC) also contributes to SDE but has received less attention due to uncertainty and challenges in model representation. This work incorporates the SDE of absorbing organic aerosol (BrC) from biomass burning and biofuel sources into the Snow Ice and Aerosol Radiative (SNICAR) model within a variant of the Community Earth System Model. Additionally, 12 different emission regions of BrC and BC from biomass burning and biofuel sources are tagged to quantify the relative contribution to global and regional SDE. BrC global SDE (0.021–0.056 Wm −2 over land area and 0.0061–0.016 Wm −2 over global area) is larger than other model estimates, corresponding to 37%–98% of the SDE from BC. When compared to observations, BrC simulations have a range in median bias (−2.5% to +21%), with better agreement in the simulations that include BrC photochemical bleaching. The largest relative contributions to global BrC SDE are traced to Northern Asia (23%–31%), Southeast Asia (16%–21%), and South Africa (13%–17%). Transport from Southeast Asia contributes nearly half of the regional BrC SDE in Antarctica (0.084–0.3 Wm −2 ), which is the largest regional input to global BrC SDE. Lower latitude BrC SDE is correlated with snowmelt, in‐snow BrC concentrations, and snow cover fraction, while polar BrC SDE is correlated with surface insolation and snowmelt. This indicates the importance of in‐snow processes and snow feedbacks on modeled BrC SDE. Plain Language Summary: Bright surfaces like snow and ice reflect some of the sun's light back to space, leading to less surface warming. These reflective surfaces can be coated by light absorbing particles such as soot and dust, reducing their reflectivity and speeding up the warming of the climate. "Brown carbon" is another absorbing particle that also darkens these surfaces. Fewer studies have looked at this climate effect due to challenges in modeling brown carbon (BrC) in the atmosphere and on snow. Here, a more detailed treatment of BrC from fires is added to a global climate model to understand how BrC affects snow reflectivity. This model also keeps track of where the BrC in smoke is released to understand how different parts of the world impact snow surfaces. One of the main findings of this work is that BrC is better at darkening snow surfaces than previous work has shown. When compared to soot–which is the strongest snow darkening agent–BrC has a comparable effect, ranging from around half to the same darkening of snow surfaces as soot. Additionally, BrC from large fires in close proximity to snow has largest impacts on snow reflectivity. Key Points: Brown carbon (BrC) forcing on snow is larger than in previous modeling studies and is comparable to the snow darkening effect (SDE) of black carbon Northern Asia, Southeast Asia, and Southern Africa are the largest source contributors to global BrC SDE Seasonal BrC is closely correlated with snow processes in the model, indicating the importance of aerosol‐snow feedbacks